Bilateral popliteal artery injury: Lessons learned. (October 2019) - Musonza, Tashinga; Khouqeer, Ahmed; Gilani, Ramyar
Abstract: Popliteal artery trauma is reported to have the highest rates of limb loss in peripheral vascular injuries. It can be inferred that morbidity associated with bilateral popliteal artery trauma is worse. However, bilateral popliteal artery injuries are sparsely reported in literature and as such management options are not well defined. Despite the paucity of reported cases, a systematic and deliberate approach to these devastating injuries may result in reproducible limb salvage. We hereby use our case report as a provocateur to this conundrum. Consideration should be given to the utilization of surgical shunts or a two-surgical team and limb salvage attempted till proving the neurovascular bundle irreparable. Arterial grafts should be part of the surgeon's armamentarium. In massive hard to control hemorrhage, tourniquets or resuscitative endovascular occlusion devices (REBOA) may prove lifesaving. Larger studies are needed to define contemporary management and derive management guidelines.